PENINGKATAN KEAKTIFAN BELAJAR DAN PRESTASI BELAJAR MELALUI PENERAPAN MODEL TEAM GAME TURNAMENT (TGT) PADA MATA PELAJARAN TEKNOLOGI MEKANIK SISWA KELAS X MESIN 1 SMK PANCASILA SURAKARTA TAHUN PELAJARAN 2014/2015 - Agung Wibowo, Muhammad Ari (Jurnal Nosel, 2015)
The aim of this research is to improve learning achievment and learning participation of student learning on the study the Teknologi Mekanik in class X Mesin 1 SMK Pancasila Surakarta through the application of the model Team Game Turnament (TGT). This research is a classroom action research (CAR). The results show that through the application of the model Team Game Turnament (TGT) can improve learning achievment and learning participation of pre-cycle to cycle I and II. The learning process in the pre-cycle using the conventional model so that the students' learning and paticipation lower. The increase occurred in the first cycle a value of students who achieve mastery in the pre-cycle as much as 40.44% increase to 70.07%. Furthermore, on the second cycle increased to 92,59%. For the participationly of students in the observation sheet increased from pre-cycle by 48,14% to 74,08% and the second cycle increased to 92,59%. The conclusions of this research is the application of the Team Game Turnament (TGT) can improve learning achievment and participation of students of class X Mesin 1 SMK Pancasila Surakarta.